Engineering lymphocyte subsets: tools, trials and tribulations - June, Carl H. (2009)
Cell-based therapies with various lymphocyte subsets hold promise for the treatment of several diseases, including cancer and disease resulting from inflammation and infection. The ability to genetically engineer lymphocyte subsets has the potential to improve the natural immune response and correct impaired immunity. In this Review we focus on the lymphocyte subsets that have been modified genetically or by other means for therapeutic benefit, on the technologies used to engineer lymphocytes and on the latest progress and hurdles in translating these technologies to the clinic.